The impact of HENRY on parenting and family lifestyle: A national service evaluation of a preschool obesity prevention programme. (July 2016) - Willis, T.A.; Roberts, K.P.J.; Berry, T.M.; Bryant, M.; Rudolf, M.C.J.
Abstract: Objectives: One in five children in England are overweight/obese at school entry. Tackling obesity is therefore a priority. Right from the Start with HENRY is a widely-commissioned programme delivered by trained facilitators to small groups of parents over eight weekly sessions. It is designed to provide parents of infants and preschool children with the skills, knowledge and confidence required for a healthier family lifestyle. The aim of this work was to investigate programme impact using data collected routinely for quality control purposes. Study design: Analysis of routinely collected pre-post data from programmes delivered in the UK from January 2012 to February 2014. Methods: Data were analysed from 144 programmes, including questionnaires relating to parenting, family eating behaviours, dietary intake, and physical activity/screen time. Results: Over 24 months, 1100 parents attended programmes running in 86 locations. 788 (72%) completed >5 sessions of whom 624 (79%) provided baseline and completion questionnaires. Parents reported increases in healthiness of family lifestyle, parenting attributes, and emotional wellbeing following attendance (all P < .001). Both parents and children were reported to have increased their daily fruit/vegetable consumption, and reduced their consumption of high fat/sugar foods (both P < .001). There were also positive changes in eating behaviours, physical activity ( P < .001) and children's screen time ( P < .001). Conclusions: Significant changes were reported in all domains similar to those reported in a previous, smaller study in locations selected for experience and quality. The HENRY approach appears to have a beneficial impact even when delivered at scale in non-selected locations. Such changes, if maintained, may serve to protect against later obesity.